Cognitive aids and food choice: Real-time calorie counters reduce calories ordered and correct biases in calorie estimates. (1st October 2019) - Gustafson, Christopher R.; Zeballos, Eliana
Abstract: Studies of the effect of calorie information on food choices in food-away-from-home settings have identified minor to insignificant changes in calories ordered. An element of the choice process that may play an important role in influencing the total caloric content of a meal has received little attention: how individuals track the total number of calories selected when choosing multiple items. We study the effects of automating this potentially costly cognitive process using technology. We compare the number of calories ordered in a sequential food choice task in two conditions: one in which participants have access to calorie information for all options available and a second in which they are also exposed to automatically updating information about the number of calories they have ordered. Participants with access to calorie summation ordered significantly fewer calories than those without access to calorie summation. Participants without access to calorie summation significantly underestimated the number of calories they had ordered, while those in the calorie summation condition did not. The calorie summation seems to work in part through adjustment of sequential choices: calories ordered in the first choice category were very similar in the two conditions but diverged increasingly in later categories. Technologies that help individuals keep track of the nutritional consequences of cumulative choices may help promote healthier diets.